Efficient and Stable Deep‐Blue Fluorescent Organic Light‐Emitting Diodes Employing a Sensitizer with Fast Triplet Upconversion. Issue 19 (6th April 2020) - Zhang, Dongdong; Song, Xiaozeng; Gillett, Alexander J.; Drummond, Bluebell H.; Jones, Saul T. E.; Li, Guomeng; He, Hanqing; Cai, Minghan; Credgington, Dan; Duan, Lian
Abstract: Multiple donor–acceptor‐type carbazole–benzonitrile derivatives that exhibit thermally activated delayed fluorescence (TADF) are the state of the art in efficiency and stability in sky‐blue organic light‐emitting diodes. However, such a motif still suffers from low reverse intersystem crossing rates ( k RISC ) with emission peaks <470 nm. Here, a weak acceptor of cyanophenyl is adopted to replace the stronger cyano one to construct blue emitters with multiple donors and acceptors. Both linear donor–π–donor and acceptor–π–acceptor structures are observed to facilitate delocalized excited states for enhanced mixing between charge‐transfer and locally excited states. Consequently, a high k RISC of 2.36 × 10 6 s −1 with an emission peak of 456 nm and a maximum external quantum efficiency of 22.8% is achieved. When utilizing this material to sensitize a blue multiple‐resonance TADF emitter, the corresponding device simultaneously realizes a maximum external quantum efficiency of 32.5%, CIE y ≈ 0.12, a full width at half maximum of 29 nm, and a T80 (time to 80% of the initial luminance) of > 60 h at an initial luminance of 1000 cd m −2 . Abstract : Multiple donor–acceptor‐type carbazole–benzonitrile derivatives with both linear donor–π–donor and acceptor–π–acceptor structures to promote triplet upconversion are utilized as a sensitizer, realizing organic light‐emitting diodes with deep‐blue narrow‐band emission, maximum external quantum efficiency of 32.5%, and a T80 (time to 80% of the initial luminance) of >3000 h at an initial luminance of 100 cd m −2 simultaneously.